LLIN Evaluation in Uganda Project (LLINEUP2) - Effect of long-lasting insecticidal nets (LLINs) treated with pyrethroid plus pyriproxyfen vs LLINs treated with pyrethroid plus piperonyl butoxide in Uganda: A cluster-randomised trial. - Samuel Gonahasa; Jane Frances Namuganga; Martha J Nassali; Catherine Maiteki-Sebuguzi; Isaiah Nabende; Adrienne Epstein; Katherine Snyman; Joaniter I Nankabirwa; Jimmy Opigo; Martin J Donnelly; Grant Dorsey; Moses R Kamya; et al. (PLOS Global Public Health, 2025)
Long-lasting insecticidal nets (LLINs) are the cornerstone of malaria control, but their effectiveness is threatened by pyrethroid resistance. We embedded a pragmatic, cluster-randomised trial into Uganda's national LLIN distribution campaign in 2020-2021, comparing pyrethroid-piperonyl butoxide (PBO) LLINs to pyrethroid-pyriproxyfen LLINs. Target communities surrounding public health facilities (clusters, n=64), covering 32 districts were included. Clusters were randomised 1:1 in blocks of two by district to receive: (1) pyrethroid-PBO LLINs (PermaNet 3.0, n=32) or (2) pyrethroid-pyriproxyfen LLINs (Royal Guard, n=32). LLINs were delivered from 7 November 2020 to 26 March 2021. Malaria surveillance data were collected from health facilities from 1 November 2019 until 31 March 2023. Cluster-level estimates of malaria incidence in residents of all ages (primary outcome) were generated from enhanced health facility surveillance data. Cross-sectional community surveys were conducted in randomly selected households (at least 50 per cluster) at 12-months (24 November 2021 to 1 April 2022) and 24-months (23 November 2022 to 21 March 2023) post-LLIN distribution. Overall, 186,364 clinical malaria episodes were diagnosed in cluster residents during 398,931 person-years of follow-up. At 24-months, malaria incidence was lower than baseline in both arms (pyrethroid-PBO: 465 vs 676 episodes per 1000 person-years; pyrethroid-pyriproxyfen: 469 vs 674 episodes per 1000 person-years); but there was no evidence of a difference between the arms (incidence rate ratio 1.06, 95% confidence interval [CI] 0.91-1.22, p=0.47). Two years post-distribution, ownership of at least one LLIN for every two household residents was low in both arms (41.1% pyrethroid-PBO vs 38.6% pyrethroid-pyriproxyfen). Parasite prevalence in children aged 2-10 years was no different between the arms in either survey (24-months: 26.1% pyrethroid-PBO; 29.5% pyrethroid-pyriproxyfen; odds ratio 1.29 [95% CI: 0.81-2.05], p=0.29). The effectiveness of pyrethroid-PBO LLINs and pyrethroid-pyriproxyfen LLINs was no different in Uganda, but two years after mass distribution, LLIN coverage was inadequate. Trial registration: NCT04566510. Registered 28 September 2020, https://clinicaltrials.gov/ct2/show/NCT04566510.